Myocarditis and Subclinical-Like Infection Associated With SARS-CoV-2 in Two Cats Living in the Same Household in France: A Case Report With Literature Review - Chetboul, Valérie; Foulex, Pierre; Kartout, Kahina; Klein, Anne Marie; Sailleau, Corinne; Dumarest, Marine; Delaplace, Manon; Gouilh, Meriadeg Ar; Mortier, Jeremy; Le Poder, Sophie (Frontiers in Veterinary Science, 2021)
This report provides the first clinical, radiographic, echocardiographic, and biological description of SARS-CoV-2-associated myocarditis with a 6-month follow-up in a 5-year-old obese male domestic shorthair cat (Cat-1) presented for refractory congestive heart failure, with high cardiac troponin-I level (5.24 ng/ml), and a large lingual ulcer. The animal was SARS-CoV-2 positive on serology. The other cat living in the same household (Cat-2) never showed any clinical sign but was also confirmed SARS-CoV-2 positive on serology. Both cats were SARS-CoV-2 PCR negative. Cat-1 had closer contact than Cat-2 with their owner, who had been in close contact with a coworker tested PCR positive for COVID-19 (Alpha (B.1.1.7) variant) 4 weeks before Cat-1's first episode of congestive heart failure. A focused point-of-care echocardiography at presentation revealed for Cat-1 numerous B-lines, pleural effusion, severe left atrial dilation and dysfunction, and hypertrophic cardiomyopathy phenotype associated with focal pulmonary consolidations. Both myocarditis and pneumonia were suspected, leading to the prescription of cardiac medications and antibiotics. One month later, Cat-1 recovered, with normalization of left atrial size and function, and radiographic and echocardiography disappearance of heart failure signs and pulmonary lesions. An extensive literature review of SARS-CoV-2-related cardiac injury in pets in comparison with human pathology is discussed.